Wong's nursing care of infants and children - Hockenberry, Marilyn J.; Hockenberry, Marilyn J.; Wilson, David 1950 August 25-2015; Rodgers, Cheryl C. (St. Louis, Missouri Elsevier, 2019)
"Prepare to give pediatric patients the specialized care they deserve with the leading text in pediatric nursing. Written by pediatric experts, "Wong's Nursing Care of Infants and Children, 11th Edition" takes a unique, easy-to-follow developmental approach to describe the care of children at each age and stage of development. This longtime bestseller provides an evidence-based, clinical perspective that shows how the quality of nursing care can impact quality patient outcomes. Childhood diseases and disorders are organized by age groups and body systems and explained through the nursing process framework. This edition features completely updated and reorganized chapters that present content in a clear, easy-to-understand way. New Quality Indicator boxes paint a bigger picture of hospitals and how they look at quality and safety" --
Part 1. Children, their families, and the nurse -- Part 2. Childhood and family assessment -- Part 3. Family-centered care of the newborn -- Part 4. Family-centered care of the infant -- Part 5. Family-centered care of the toddler and preschooler -- Part 6. Family-centered care of the school-age child -- Part 7. Family-centered care of the adolescent -- Part 8. Family-centered care of the child with special needs -- Part 9. The child who is hospitalized -- Part 10. Childhood nutrition and elimination problems -- Part 11. Childhood oxygenation problems -- Part 12. Childhood blood production and circulation problems -- Part 13. Childhood regulatory problems -- Part 14. Childhood physical mobility problems.
Includes bibliographical references and index.
Keywords: Pediatric nursing; Infants -- Care; Child care; Pediatric Nursing; Infant Care; Child Care; Pediatric nursing; Infants -- Care; Child care; Child care; Infant care; Pediatric nursing